Coal gangue treatment method and application thereof in molecular sieve synthesis
By pulverizing, baking activation, ball milling treatment and acid treatment of coal gangue, a high activity and high silicon-aluminum ratio coal gangue precursor was prepared, which solved the problem that coal gangue was not suitable for direct use in the synthesis of high silicon molecular sieve. It realizes the efficient application of coal gangue in the synthesis of high silica zeolites.
Patent Information
- Application Number
- CN202311045892.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
AI Technical Summary
Coal gangue raw materials are not suitable for direct use in the synthesis of high-silicon molecular sieves, and their lack of controllability during activation, which makes it difficult to adjust the silicon-aluminum ratio, limiting its application in the synthesis of high-silicon zeolites.
Through the steps of crushing, calcination activation, ball milling treatment, acid treatment and centrifugal washing, a coal gangue precursor with high activity and high silicon-aluminum ratio is prepared. The method includes coordinated adjustment of calcining temperature, ball milling time, acid treatment conditions, etc., ensuring efficient activation of coal gangue and controllability of silicon-aluminum ratio.
The high activity and high silicon-aluminum ratio of coal gangue have been achieved, and its application efficiency and utilization rate in the synthesis of high silica zeolites have been improved, and it has important industrial application value.
Smart Images

Figure CN119490195A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal chemical industry, and in particular relates to a method for treating coal gangue and application thereof in molecular sieve synthesis. Background Art
[0002] The energy resource characteristics of "rich in coal, poor in oil, and little gas" determine my country's coal-based energy structure, and coal provides the foundation for the development of the national economy. However, a large amount of coal gangue will be produced in the process of coal mining, utilization, and washing. The total output of coal gangue in China has exceeded 5 billion tons, and it is still growing rapidly. The accumulation of a large amount of coal gangue not only occupies a large amount of land resources, but also causes serious environmental problems. At present, my country's utilization of coal gangue is mainly concentrated in low value-added means such as power generation, heating, and as building material additives, and the comprehensive utilization rate is less than 60%. The main components of coal gangue are SiO2 and Al2O3. How to effectively utilize its rich silicon and aluminum elements and utilize them as materials is of great significance for the high value-added utilization of coal gangue. Gangue is mainly composed of kaolinite and quartz, hematite and carbonaceous materials. Due to its composition, the activity of gangue itself is often low, and it needs to be activated by certain treatment methods such as roasting and alkali fusion. However, it is often impossible to control the high-activity silicon-aluminum ratio, and because a large amount of alkali is required to activate the gangue, the synthesis phase area is greatly limited when it is subsequently synthesized into molecular sieves. In addition, there are some treatment methods to completely purify the gangue into SiO2 and Al2O3 or corresponding components to synthesize molecular sieves, but the cost and steps are often more.
[0003] In addition, the silicon-aluminum composition of coal gangue is about 1:1, which is not suitable for direct synthesis of high-silicon molecular sieves. At present, it is mainly used to synthesize type A and type X zeolites with lower silicon-aluminum ratios. There are also studies on using it to synthesize high silicon-aluminum ratios of ZSM-5, SSZ-13, etc. However, due to the composition, it can only be used as an external Al source to replace a small amount of silicon source, and its utilization rate is very limited.
[0004] Therefore, it is of great significance to develop a pretreatment method for high-activity coal gangue precursors that can be used for the synthesis of high-silicon molecular sieves. Summary of the invention
[0005] In view of this, the present invention provides a method for treating coal gangue and its application in molecular sieve synthesis, the main purpose of which is to solve the technical problem that coal gangue raw materials are not suitable for directly synthesizing high-silicon molecular sieves.
[0006] In one aspect, the present invention provides a method for treating coal gangue, comprising the following steps:
[0007] S1, the coal gangue is crushed to obtain raw coal gangue powder;
[0008] S2, the raw coal gangue powder in step S1 is calcined and activated to obtain an activated product I;
[0009] S3, the product I in step S2 is subjected to ball milling to obtain product II;
[0010] S4, the product II in step S3 is treated with acid to obtain product III;
[0011] S5. The product III in step S4 is centrifuged and washed to obtain high-activity coal gangue.
[0012] The treated coal gangue prepared by the present invention is high-activity, high-silicon-aluminum ratio coal gangue, and is suitable for high-efficiency synthesis of high-silicon zeolite.
[0013] Optionally, in step S1, the particle size of the raw coal gangue powder is greater than 40 meshes.
[0014] Optionally, in step S2, the calcination temperature is 650°C to 850°C; the calcination time is 1h to 20h; and the calcination atmosphere is air, nitrogen or argon.
[0015] Optionally, the calcination temperature is selected from any value among 650°C, 675°C, 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C or any range therebetween.
[0016] The calcination time is selected from any value among 1h, 3h, 5h, 7h, 9h, 11h, 13h, 15h, 17h, 19h, 20h or any range between two of them.
[0017] Optionally, in step S3, the particle size of the product II is greater than 200 mesh; and the crystallinity of the product II is 5 to 70% of the crystallinity of the product I before ball milling.
[0018] Optionally, the selected ball mill speed is between 250rpm and 550rpm, the clockwise and counterclockwise alternating time interval of the ball mill is between 20min and 80min, the ratio of large, medium and small balls in the ball mill is between 1:0.5:0.1 and 1:5:10, and the ball milling time is between 2h and 16h.
[0019] Optionally, the ball mill rotation speed is selected from any value among 250rpm, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm or any range value therebetween.
[0020] The ball mill speed is selected from any value among 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h or any range between two of them.
[0021] Optionally, in step S4, the acid used in the acid treatment is selected from at least one of hydrochloric acid, nitric acid and sulfuric acid.
[0022] Optionally, in step S4, the temperature of the acid treatment is 50°C to 95°C; the solid-liquid mass ratio of the product II to the acid in step S3 is 1:10 to 1:50; the acid treatment time is 0.5h to 5h; and the mass concentration of the acid is 10wt% to 40wt%.
[0023] Optionally, in step S4, the temperature of the acid treatment is 75°C to 95°C.
[0024] Optionally, the temperature of the acid treatment is selected from any value of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 77.5°C, 80°C, 82.5°C, 85°C, 87.5°C, 90°C, 92.5°C, 95°C or any range therebetween.
[0025] The time of the acid treatment is independently selected from any value of 0.5 h, 1.0 h, 1.5 h, 2.0 h, 2.5 h, 3.0 h, 3.5 h, 4.0 h, 4.5 h, 5.0 h, or any range therebetween.
[0026] Optionally, in step S5, the pH value of the centrifugal washing liquid after the product III is centrifuged and washed is 6.0-7.5.
[0027] The centrifugal washing liquid of the present invention refers to the liquid separated after the last round of centrifugal washing, and its pH value is 6.0-7.5.
[0028] Optionally, in step S5, the silicon-aluminum ratio of the treated coal gangue is greater than 5, calculated as SiO2 / Al2O3.
[0029] Preferably, the silicon-to-aluminum ratio of the treated coal gangue is greater than 8, calculated as SiO2 / Al2O3.
[0030] Optionally, step S4 and step S5 may be repeated to improve the silicon-aluminum ratio of the prepared high-activity coal gangue.
[0031] The coal gangue prepared by the pretreatment method provided by the present invention can be adjusted within a wide range of silicon-aluminum ratios, and the silicon-aluminum ratio adjustment (i.e., the degree of dealumination) of the final product can be controlled by changing the conditions in a series of pretreatment means, such as adjusting the roasting temperature, solid-liquid ratio, acid concentration, ball milling and other detailed conditions, which will change the performance of the final product. It can also be adjusted accordingly according to the requirements of the specific target product. For example, for CHA zeolite with an important commercial background, it has a relatively excellent NH3-SCR activity after exchanging a suitable Cu content within a relatively low silicon-aluminum ratio range (still higher than natural low silicon-aluminum ratio zeolite), and the precursor can be controlled within the range of (Si / Al=8-15) to obtain a more excellent reaction activity. In addition, if it is necessary to use it for methanol to olefins (MTO) reaction, it is necessary to appropriately increase the silicon-aluminum ratio to reduce the acid content of the molecular sieve, and more stringent pretreatment conditions can be used to obtain a precursor with an extremely high silicon-aluminum ratio for the synthesis of high-silicon CHA to obtain good MTO catalytic performance.
[0032] The above-mentioned calcination-ball milling-acid treatment steps of the present invention have a synergistic effect: ball milling and calcination can activate the silicon-aluminum connection inside the coal gangue, the calcination activation can convert the inert kaolinite phase in the coal gangue into a metakaolinite phase, and the ball milling activation can break the chemical bonds such as Si-O and Al-O by high-energy mechanical means, thereby further reducing the crystallinity and increasing the activity, which is beneficial to the subsequent acid treatment, improves the efficiency of acid de-Al, and realizes the acquisition of coal gangue with an extremely high silicon-aluminum ratio.
[0033] The calcination-ball milling-acid treatment steps in the pretreatment method of the present invention are indispensable and have a sequence. It is difficult to achieve the purpose of high silicon-aluminum ratio by changing the sequence. The crystal phase transformation in the coal gangue after calcination can improve the efficiency of subsequent ball milling and acid treatment, and control modulation can be achieved in a larger range. The ball milling after calcination is indispensable for reducing the particle size and adjusting the coordination environment of microscopic Si and Al. High-energy ball milling also promotes the improvement of acid treatment efficiency for the formation of defects and the adjustment of the microscopic chemical environment.
[0034] The pretreatment method of the present invention realizes the controllable preparation of high-activity precursors from coal gangue through the synergistic effects of thermal activation, high-energy mechanical activation and chemical treatment, which is of great significance for realizing high value-added utilization of coal gangue.
[0035] In a second aspect, the present invention provides a high-activity coal gangue obtained by the above-mentioned treatment method.
[0036] In a third aspect, the present invention provides a method for using high-activity gangue obtained by the above-mentioned gangue treatment method as a silicon-aluminum source in the synthesis of molecular sieves.
[0037] In a fourth aspect, the present invention provides a method for synthesizing a CHA molecular sieve, the method comprising:
[0038] S1: dealuminated activated coal gangue, sodium salt, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide are dissolved in deionized water to form a gel mixture;
[0039] S2: the gel mixture in step S1 is subjected to a hydrothermal reaction under closed conditions to obtain a molecular sieve having a CHA framework structure after crystallization;
[0040] Wherein, the dealuminated activated coal gangue is high-silicon coal gangue obtained by the coal gangue treatment method according to any one of claims 1 to 8.
[0041] Optionally, in step S1, the mass ratio of the dealuminized activated coal gangue, the sodium salt, the dealuminized activated coal gangue, the sodium salt, the N,N,N-trimethyl-1-adamantyl ammonium hydroxide and the deionized water is 100:(0-18.6):(126-378):(247-618).
[0042] Optionally, the molecular sieve having a CHA framework structure in step S2 has a silicon-to-aluminum ratio of 8 to 50, calculated as SiO2 / Al2O3.
[0043] Optionally, in step S1, the molar ratio of each component in the gel mixture is:
[0044] SiO2:Al2O3:Na2O:TMAdaOH:H2O=100:(2~12.5):(2~20):
[0045] (3~30): (2000~5000); wherein TMAdaOH is N,N,N-trimethyl-1-adamantyl ammonium hydroxide with a concentration of 25wt%.
[0046] Optionally, the temperature of the hydrothermal reaction in step S2 is 160-180° C., and the reaction time is 24-144 h.
[0047] In a fifth aspect, the present invention provides a method for synthesizing an MFI molecular sieve, the method comprising:
[0048] S1: dealuminated activated coal gangue and tetrapropylammonium hydroxide are dissolved in deionized water to form a gel mixture;
[0049] S2: the gel mixture in step S1 is subjected to a hydrothermal reaction under closed conditions to obtain a molecular sieve having an MFI framework structure after crystallization;
[0050] Wherein, the dealuminated activated coal gangue is high-silicon coal gangue obtained by the coal gangue treatment method according to any one of claims 1 to 8.
[0051] Optionally, in step S1, the mass ratio of the dealuminated activated coal gangue, the tetrapropylammonium hydroxide and the deionized water is 100:(364-728):(247-544).
[0052] Optionally, the molecular sieve with an MFI framework structure in step S2 has a silicon-to-aluminum ratio of 20 to 50, calculated as SiO2 / Al2O3.
[0053] Optionally, the molar ratio of each component in the gel mixture in step S1 is:
[0054] SiO2:Al2O3:TPAOH:H2O=100:(2-5):(30-50):(2000-4400);
[0055] Wherein, TPAOH is tetrapropylammonium hydroxide, and the concentration is 25wt%.
[0056] Optionally, the temperature of the hydrothermal reaction in step S2 is 140-190° C., and the reaction time is 10-48 hours.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] 1) The coal gangue pretreatment method provided by the present invention can prepare a high-activity, high-silicon-aluminum ratio coal gangue precursor, which is helpful to achieve high added value utilization of coal gangue and synthesize zeolite with important industrial application value.
[0059] 2) The coal gangue pretreatment method provided by the present invention can greatly improve the utilization rate of the synthetic molecular sieve from coal gangue, and realize that 100% of the silicon-aluminum raw materials of the synthetic molecular sieve come from coal gangue. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 The XRD diagrams of the coal gangue after dealuminization and activation and the original coal gangue powder in Example 1 of the present invention;
[0061] Figure 2 The coal gangue after dealuminization activation and the coal gangue raw powder in Example 1 of the present invention are 29 Si MAS NMR spectrum;
[0062] Figure 3 The coal gangue after dealuminization activation and the coal gangue raw powder in Example 1 of the present invention are 27 Al MAS NMR spectrum;
[0063] Figure 4 is the XRD pattern of sample 21 of Example 21 of the present invention;
[0064] Figure 5This is a scanning electron microscope (SEM) photograph of sample 21 of Example 21 of the present invention, with a scale of 10 μm;
[0065] Figure 6 This is the XRD diagram of sample 22 of comparative example 1 of the present invention. DETAILED DESCRIPTION
[0066] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0067] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0068] The analysis method in the examples of this application is as follows:
[0069] The elemental composition was determined using a Philips Magix 2424 X-ray fluorescence analyzer (XRF).
[0070] X-ray powder diffraction phase analysis (XRD) was performed using an X'Pert PRO X-ray diffractometer from PANalytical of the Netherlands, with a Cu target, a Kα radiation source (λ=0.15418 nm), a voltage of 40 kV, and a current of 40 mA.
[0071] Scanning electron microscopy (SEM) tests were performed using a Hitachi SU8020 field emission scanning electron microscope with an accelerating voltage of 2 kV.
[0072] 27 Al MAS NMR and 29 Si MAS NMR experiments were performed on a Bruker Advance III 500 MHz (11.7 T).
[0073] The ball mill used in the embodiment of the present invention is a QM-3SP2 planetary ball mill produced by Nanjing University Instrument Factory.
[0074] Examples 1 to 20 (Pretreatment of Coal Gangue Activation)
[0075] The different activation pretreatment conditions of coal gangue are shown in Table 1; the specific treatment process is as follows:
[0076] A certain amount of raw coal gangue powder is taken, and calcined at 750°C for 10 hours in a muffle furnace under air atmosphere. After calcination, it is taken out and placed in a planetary ball mill for ball milling. The ratio of large, medium and small ball milling beads is selected as 1:1:1, the rotation speed is selected as 550rpm, the clockwise and counterclockwise rotation interval is 60min, and the ball milling is performed for 6 hours. After ball milling, the ball-milled coal gangue is taken out for acid treatment, and hydrochloric acid with a mass concentration of 20wt% and a solid-liquid ratio of 1:20 is selected. After treatment at 80°C for 3h, it is washed to pH~7.0, dried and set aside to obtain dealuminized activated coal gangue.
[0077] The particle size of the solids prepared after the ball milling step in all the examples was greater than 200 mesh, and the crystallinity of the samples after ball milling was 5-70% of that before ball milling.
[0078] Taking Example 1 as an example, the XRD pattern of the dealuminated activated coal gangue prepared therein is as follows: Figure 1 As shown, the coordination information of Si and Al is as follows Figure 2 and Figure 3 As shown; the composition of the dealuminated activated coal gangue of Examples 1 to 20 is shown in Table 1.
[0079] Figure 2 The coordination of Si in gangue and gangue after dealuminization activation is shown. The peaks of original gangue are concentrated at -108ppm, -101ppm and -92ppm, belonging to Q4(0Al), Q4(1Al) and Q3(0Al) respectively. Q3(0Al) mainly exists in kaolinite and mica, Q4(1Al) mainly exists in some clay materials, and Q4(0Al) represents a typical quartz phase Si environment. After pretreatment and dealuminization, the Si environment of gangue changes significantly. Q4(0Al) and Q4(1Al) are largely converted into Si-OH corresponding to -92ppm. At the same time, the overall change of Si environment also indicates that the polymerization degree of gangue is reduced.
[0080] Figure 3 The coordination of Al in coal gangue and coal gangue after dealuminization activation is shown. The untreated coal gangue is mainly composed of hexacoordinated Al near 0ppm and tetracoordinated broad peaks near 68ppm. The wide peak shape also indicates that the Al-O polyhedral structure is asymmetric. After activation, the asymmetry is reduced and it is mainly converted into hexacoordinated Al. 3+ state.
[0081] Table 1. Gangue activation pretreatment conditions
[0082]
[0083] *Calculated based on SiO2 / Al2O3;
[0084] The silicon-aluminum ratio in the raw material of coal gangue is 1:1, and it can be seen from the experimental data in Table 1 that the silicon-aluminum ratio of the coal gangue pretreated by the method of the present invention is between 10 and 50, and the silicon-aluminum ratio is greatly improved. The treated coal gangue has the characteristics of a high silicon-aluminum ratio.
[0085] Example 21 (Preparation of CHA Molecular Sieve)
[0086] The pretreated activated gangue precursor is used to synthesize CHA zeolite. The specific pretreatment method and batching process are as follows:
[0087] Take 3.0g of dealuminized activated coal gangue obtained in Example 1, 6.375g of sodium hydroxide (10wt%), and 4.521g of N,N,N-trimethyl-1-adamantyl ammonium hydroxide (TMAdaOH) (25wt%), dissolve them in 8.519g of deionized water and stir for 2 hours.
[0088] The final gel molar ratio is 100SiO2∶5.3Al2O3∶18Na2O∶12TMAdaOH∶2200H2O.
[0089] The mixture was transferred into a stainless steel reactor and crystallized at 175°C under autogenous pressure for 36 hours. After the crystallization, the solid and liquid were separated and washed to neutrality, and dried at 100°C for 10 hours, which was recorded as sample 21.
[0090] The X-ray powder diffraction pattern (XRD) of sample 21 is as follows: Figure 4 As shown, it is shown that the sample is a molecular sieve with a CHA framework structure.
[0091] The scanning electron microscope (SEM) image of sample 21 is as follows: Figure 5 As shown, the particles of the sample are typical CHA cubic morphology, with a size of about 1 μm to 2 μm. The composition of the product is SiO2 / Al2O3=15.2 after XRF analysis.
[0092] Example 22 (Preparation of MFI molecular sieve)
[0093] The pretreated activated gangue precursor is used to synthesize MFI zeolite. The specific pretreatment method and batching process are as follows:
[0094] Take 3.2 g of dealuminated activated coal gangue obtained in Example 1 and 12.2 g of tetrapropylammonium hydroxide TPAOH (25 wt %), dissolve them in 5.3 g of deionized water and stir for 12 hours.
[0095] The final gel ratio is 100SiO2: 2.1Al2O3: 0.3TPAOH: 2000H2O. The above mixture is transferred into a stainless steel reactor and rotated for crystallization at 180°C under autogenous pressure for 48 hours. After the crystallization, the solid and liquid are separated and washed to neutrality, and dried at 100°C for 10 hours to obtain a pure phase MFI molecular sieve; the composition of the product is SiO2 / Al2O3=43 according to XRF analysis.
[0096] Comparative Example 1
[0097] The specific preparation process is the same as the preparation of sample 21 in Example 21, except that the silicon source used is silica sol, the aluminum source is sodium aluminate, and the crystallization time is the same as that in Example 21.
[0098] The synthesized sample is recorded as sample 22. The XRD pattern of sample 22 is shown in Figure 6 As shown; the results show that the obtained sample is in an amorphous state.
[0099] By comparing sample 21 of Example 21 and sample 22 of Comparative Example 1, it is shown that the pretreated coal gangue of the present invention can realize the synthesis of CHA molecular sieve in a shorter crystallization time and has a higher silicon-aluminum ratio of 15.2.
[0100] The above comparison shows that the activity and microscopic coordination state of the pretreated coal gangue in the embodiment of the present invention are greatly different from those of the conventional silicon-aluminum source, and high-efficiency and high-activity synthesis can be achieved.
[0101] Comparative Examples 2 to 4
[0102] The specific pretreatment process of coal gangue is the same as that of Example 1, except that comparative example 2 is directly subjected to acid treatment without calcination and ball milling, comparative example 3 is not subjected to ball milling, and comparative example 4 is not subjected to calcination, and other conditions are the same. The specific silicon-aluminum ratio of the treated coal gangue is shown in Table 3.
[0103] It can be seen from the experimental tests in Table 3 that if the coal gangue does not undergo a complete and sequential roasting, ball milling and acid treatment process, its silicon-aluminum ratio will be significantly low.
[0104] Table 3. Silicon-aluminum ratio of coal gangue after pretreatment
[0105] Comparative Example <![CDATA[Processed silica-alumina ratio (SiO2 / Al2O3) <!-- 6 -->]]> 2 4.6 3 7.2 4 6.8
[0106] The silicon-aluminum ratio in the raw material of coal gangue is 1:1, the silicon-aluminum ratio of the coal gangue pretreated by the method of the present invention is between 10 and 50, and the silicon-aluminum ratio of the coal gangue of Examples 2 to 4 that has not been completely and orderly treated is between 4.6 and 7.2; it can be seen that the silicon-aluminum ratio of the coal gangue after the complete and orderly treatment steps of the present invention is significantly higher than the silicon-aluminum ratio of the untreated or incompletely treated coal gangue, and the coal gangue treated by the present invention has the characteristic of obvious high silicon-aluminum ratio.
[0107] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for treating coal gangue, characterized in that: The following steps are involved: S1, the coal gangue is crushed to obtain raw coal gangue powder; S2, the raw coal gangue powder in step S1 is calcined and activated to obtain an activated product I; S3, the product I in step S2 is subjected to ball milling to obtain product II; S4, the product II in step S3 is treated with acid to obtain product III; S5. The product III in step S4 is centrifuged and washed to obtain high-activity coal gangue.
2. The method for treating coal gangue according to claim 1, characterized in that: In step S1, the particle size of the raw coal gangue powder is greater than 40 mesh; Preferably, in step S2, the calcination temperature is 650°C to 850°C; the calcination time is 1h to 20h; the calcination atmosphere is air, nitrogen or argon; Preferably, in step S3, the particle size of the product II is greater than 200 mesh; the crystallinity of the product II is 5 to 70% of the crystallinity of the product I before ball milling; Preferably, in step S4, the acid used in the acid treatment is at least one selected from hydrochloric acid, nitric acid and sulfuric acid.
3. The method for treating coal gangue according to claim 1, characterized in that: In step S4, the temperature of the acid treatment is 50°C to 95°C; the solid-liquid mass ratio of the product II to the acid in step S3 is 1:10 to 1:50; the acid treatment time is 0.5h to 5h; and the mass concentration of the acid is 10wt% to 40wt%.
4. The method for treating coal gangue according to claim 1, characterized in that: In step S5, the pH value of the centrifugal washing liquid after the product III is centrifuged and washed is 6.0-7.5; Preferably, in step S5, the silicon-aluminum ratio of the high-activity coal gangue is greater than 5, calculated as SiO2 / Al2O3; Preferably, in step S5, the silicon-aluminum ratio of the high-activity coal gangue is greater than 8, calculated as SiO2 / Al2O3.
5. A high-activity coal gangue, characterized in that: The high-activity coal gangue is prepared by the treatment method described in any one of claims 1 to 4.
6. Use of the high-activity gangue obtained by the gangue treatment method according to any one of claims 1 to 4 as a silicon-aluminum source in the synthesis of molecular sieves.
7. A method for synthesizing a CHA molecular sieve, characterized in that: The method comprises: S1: dealuminated activated coal gangue, sodium salt, and N,N,N-trimethyl-1-adamantyl ammonium hydroxide are dissolved in deionized water to form a gel mixture; S2: the gel mixture in step S1 is subjected to a hydrothermal reaction under closed conditions to obtain a molecular sieve having a CHA framework structure after crystallization; Wherein, the dealuminated activated coal gangue is high-activity coal gangue obtained by the coal gangue treatment method according to any one of claims 1 to 4.
8. The method for synthesizing CHA molecular sieve according to claim 7, characterized in that: In step S1, the mass ratio of the dealuminated activated coal gangue, the sodium salt, the N,N,N-trimethyl-1-adamantyl ammonium hydroxide and the deionized water is 100:(0-18.6):(126-378):(247-618); Preferably, the molecular sieve having a CHA framework structure in step S2 has a silicon-to-aluminum ratio of 8 to 50, calculated as SiO2 / Al2O3; Preferably, in step S1, the molar ratio of the components in the gel mixture is: SiO2:Al2O3:Na2O:TMAdaOH:H2O=100:(2~12.5):(2~20): (3~30):(2000~5000); Wherein, TMAdaOH is N,N,N-trimethyl-1-adamantyl ammonium hydroxide, and the concentration is 25wt%; Preferably, the temperature of the hydrothermal reaction in step S2 is 160-180° C., and the reaction time is 24-144 h.
9. A method for synthesizing an MFI molecular sieve, characterized in that: The method comprises: S1: dealuminated activated coal gangue and tetrapropylammonium hydroxide are dissolved in deionized water to form a gel mixture; S2: the gel mixture in step S1 is subjected to a hydrothermal reaction under closed conditions to obtain a molecular sieve having an MFI framework structure after crystallization; Wherein, the dealuminated activated coal gangue is high-silicon coal gangue obtained by the coal gangue treatment method according to any one of claims 1 to 8.
10. The method for synthesizing the MFI molecular sieve according to claim 9, characterized in that: In step S1, the mass ratio of the dealuminated activated coal gangue, the tetrapropylammonium hydroxide and the deionized water is 100:(364-728):(247-544); Preferably, the molecular sieve having an MFI framework structure in step S2 has a silicon-to-aluminum ratio of 20 to 50, calculated as SiO2 / Al2O3; Preferably, the molar ratio of each component in the gel mixture in step S1 is: SiO2:Al2O3:TPAOH:H2O=100:(2-5):(30-50):(2000-4400); Wherein, TPAOH is tetrapropylammonium hydroxide, and the concentration is 25wt%; Preferably, the temperature of the hydrothermal reaction in step S2 is 140-190° C., and the reaction time is 10-48 hours.
Citation Information
Patent Citations
ZSM-5 molecular sieve and preparation method thereof
CN104743573A
Method for preparing CHA molecular sieve by taking gangue as silicon-aluminium sources
CN105948070A
Method of preparing mesoporous material from coal gangue and catalyst carrier prepared from coal gangue
CN109909274A
Cited By
Aluminum-based hydrotalcite synthesized by solid waste coal gangue in-situ crystallization and preparation method and application thereof
CN120864542A